New characterizations of k-normal and k-EP matrices - ZhiMei Fu; Kezheng Zuo; Yang Chen (Kuwait Journal of Science)
In this paper, some new characterizations of k-normal and k-EP matrices are obtained using the core-EP decomposition. We obtain several equivalent conditions for a matrix A to be k-normal and k-EP in terms of certain generalized inverses.